Description of Science Teacher Readiness in Implementing Independent Curriculum at SMAN 1 Pulau Maya - Agustina, Bella; Enawaty, Eny; Ifriany, Andi; Hairida, Hairida; Erlina, Erlina (Universitas Pendidikan Mandalika, 2024)
This study aims to evaluate the readiness of science teachers at State Senior High School (SMAN) 1 Pulau Maya in implementing the Merdeka Curriculum, with a focus on understanding the curriculum and readiness in developing teaching modules. The method used is descriptive qualitative, with data collection through observation, interviews, and documentation of three science teachers (Chemistry, Biology, and Physics). The results showed that the teachers' understanding of the curriculum reached excellent scores, namely 100 for Chemistry, 100 for Biology, and 93.8 for Physics, with an average of 98. However, their readiness in preparing teaching modules was at a sufficient level, with a percentage of 55% for Chemistry, 67% for Biology, and 72% for Physics, an average of 65% thus classified as ready. In conclusion, although science teachers have understood the curriculum well, there is still a need to improve their readiness in preparing teaching modules in order to carry out the learning process optimally.